Abnormal increase of TCP phase during heat treatment in a Ni-based single crystal superalloy. (December 2019) - Yin, Bin; Xie, Guang; Lou, Langhong; Zhang, Jian
Abstract: Generally, elevated solution heat treatment temperature decreases the residual dendritic segregation of refractory elements (i.e. Re and W) and suppresses the precipitation of deleterious topologically close-packed (TCP) phases in Ni-based superalloys. However, in the present study, elevated solution temperature resulted in an abnormal increase of TCP phases in a Ni-based single crystal superalloy after long-term thermal exposure at 900 °C. Microstructural analysis suggested that higher supersaturation in γ phase which promoted the formation of TCP phases was induced by the increased γ′ precipitation after heat treated at elevated solution temperature. Graphical abstract: Unlabelled Image